Global HIV prevention, treatment, and care interventions and strategies for key populations: Protocol for a scoping review - Emmanuel Kumah; Dorothy Serwaa Boakye; Eunice Agyei; Richard Boateng; Veronica Penaman Asamoah; Emmanuel Osei Tutu (PLoS ONE, 2025)
Introduction Since its emergence, HIV/AIDS has remained one of the most significant global health challenges, with key populations—such as sex workers, men who have sex with men (MSM), transgender people, people who inject drugs (PWID), and individuals in prisons or other closed settings—disproportionately bearing the burden of the epidemic. These groups, often at heightened risk due to social, legal, and structural vulnerabilities, face persistent barriers to accessing prevention, treatment, and care services. Despite progress in reducing new infections and improving treatment outcomes, these disparities, exacerbated by stigma, structural inequalities, and insufficient political commitment, continue to limit the effectiveness of global HIV responses. Aim This scoping review protocol aims to systematically map the range of HIV prevention, treatment, and care interventions and strategies targeting key populations worldwide. Rather than formally evaluating effectiveness, the review will describe the nature, extent, and types of interventions implemented, identify barriers to implementation, and highlight gaps in research and practice. Methods Following the Joanna Briggs Institute (JBI) guidelines for scoping reviews, the study will systematically identify and analyze evidence from multiple databases, including PubMed, Embase, CINAHL, Scopus, and PsycINFO, alongside regional and grey literature sources. The review will include studies focusing on key populations and evidence-based interventions, such as prevention tools, treatment strategies, and policy or structural interventions. Data will be extracted and synthesized using quantitative and qualitative approaches, with results presented through descriptive statistics and thematic analysis. Findings will inform the development of a comprehensive, evidence-based framework tailored to the unique needs of key populations. Conclusion By mapping available interventions and strategies for HIV prevention, treatment, and care among key populations, this review will provide a comprehensive overview of existing approaches, barriers, and gaps. The findings will inform future research, policy, and practice, supporting more targeted, inclusive, and sustainable HIV responses that contribute to global efforts to end AIDS as a public health threat by 2030.